Pengaruh Employer Branding dan Kompensasi terhadap Minat Melamar Kerja pada Generasi Z di Daerah Istimewa Yogyakarta - Aisyah Nur Jannavi; Kristiana Sri Utami (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to examine the influence of employer branding and compensation on job application interest among Generation Z in the Special Region of Yogyakarta. The background of this research is the phenomenon known as the